On numerical solutions of time-fraction generalized Hirota Satsuma coupled KdV equation - Aslan, Ebru Cavlak; İnç, Mustafa; Al Qurashi, Maysaa' Mohamed; Baleanu, Dumitru (Int Scientific Research Publications, 2017)
In this study, we obtain the approximate soliton solution of the fractional generalized Hirota-Satsuma coupled Kortewegde Vries equation (GHS-cKdV) within the homotopy analysis method (HAM). Numerical results are successfully compared with other solutions obtained by the differential transform method (DTM) and the homotopy perturbation method (HPM). The numerical results indicate that the only few terms are sufficient to get the correct solutions. Also, the results are given by tables and figures. (C) 2017 All rights reserved.
Keywords: HAM; fractional partial differential equation(FPD); HS-cKdV equation; time-fractional GHS-cKdV equation